2022
DOI: 10.1093/g3journal/jkac215
|View full text |Cite
|
Sign up to set email alerts
|

The improved genome of the nematode Parapristionchus giblindavisi provides insights into lineage-specific gene family evolution

Abstract: Nematodes such as Caenorhabditis elegans and Pristionchus pacificus are extremely successful model organisms for comparative biology. Several studies have shown that phenotypic novelty but also conserved processes are controlled by taxon-restricted genes. To trace back the evolution of such new or rapidly evolving genes, a robust phylogenomic framework is indispensable. Here, we present an improved version of the genome of Parapristionchus giblindavisi which is the only known member of the sister group of Pris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The completeness of the R. inermis genome was estimated by BUSCO to be 88.8% (single-copy and duplicates) using the nematode ortholog data set (odb9) [38,39]. This value is comparable to recently generated nematode genome assemblies from cultures without large-scale microbial contamination [41,42]. Note that the expected BUSCO completeness value should be around 90%, but will also depend on evolutionary distance from the set of reference species in the ortholog set.…”
Section: R Inermis Has Five Chromosomes With Near-complete Coverage B...mentioning
confidence: 89%
See 1 more Smart Citation
“…The completeness of the R. inermis genome was estimated by BUSCO to be 88.8% (single-copy and duplicates) using the nematode ortholog data set (odb9) [38,39]. This value is comparable to recently generated nematode genome assemblies from cultures without large-scale microbial contamination [41,42]. Note that the expected BUSCO completeness value should be around 90%, but will also depend on evolutionary distance from the set of reference species in the ortholog set.…”
Section: R Inermis Has Five Chromosomes With Near-complete Coverage B...mentioning
confidence: 89%
“…Previous phylogenetic studies suggested a potential sister taxon relationship between R. inermis and the family Diplogastridae [26,27]. To resolve the phylogenetic relationship between R. inermis and diplogastrid nematodes, we compiled a phylogenomic data set of annotated proteins and transcriptomes from 40 species [41,42,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. We employed a previously established phylogenomic pipeline for reconstructing a species tree from this type of data [70].…”
Section: Phylogenomic Analysis Does Not Support R Inermis As a Sister...mentioning
confidence: 99%
“…We searched the genomes of ten nematode species for orthologs of Ppa-NHR-1, Ppa-NHR-10, and Ppa-NHR-40, using BLASTP (e < 0.0001). The list of genomes included Brugia malayi (clade III -Spiruromorpha), Bursaphelenchus xylophilus (clade IV -Tylenchida), Panagrellus redivivus (clade IV -Tylenchida), Oscheius tipulae (clade V -Rhabditida), Caenorhabditis briggsae (clade V -Rhabditida), Caenorhabditis elegans (clade V -Rhabditida; wormbase.org WS289), Haemonchus contortus (clade V -Strongylida), Micoletzkya japonica (clade V -Diplogasterida), Parapristionchus giblindavisi (clade V -Diplogasterida), and Pristionchus pacificus (clade V -Diplogasterida) [97][98][99][100][101][102][103][104][105][106] (non-diplogastrids: WormBase ParaSite ver. WBPS18; diplogastrids: pristionchus.org).…”
Section: Phylogram Of the Nhr-1/-10/-40 Clustermentioning
confidence: 99%
“…The 24 basepair region between the genomic coordinates 2633305 and 2633328 on chromosome X of P. pacificus (Rödelsperger et al, 2017) was a perfect and unique match against our query sequence. Next, leveraging the availability of sequenced genomes of other species in the family Diplogastridae (Prabh et al, 2018;Röseler et al, 2022;Wighard et al, 2022;Yoshida et al, 2023), the 24-nucleotide read was queried against and gave perfect matches in eight of the 10 genomes. The two exceptions were Pristionchus fissidentatus, where the match was limited to the first 23 nucleotides, and Pristionchus mayeri, where no match was found.…”
Section: Introductionmentioning
confidence: 99%